Assessing the status of physical and health education in Ibadan metropolitan schools (2008)
The study assessed the status of physical and health education in Ibadan metropolis. Sixty-one PHE teachers were randomly selected from fifty secondary schoold in the city. Ateacher questionnaire was administered on the respondents and the data analysed using frequency counts, percentages and t-test. The status of PHE in the schools is that the subject is taught and there are teachers tot each it in many sampled schools in the metroplis. Sixty-nine percent of the schools have 2 or 3 teachers and 15% have between 4 and 8 teachers teaching the subject. The teacher profile shows that 52. 5% are females and 47.5% are males. Sixty-eight percent are first degree graduates, 20% N. C. E of which 39% have been teaching for over 21 years, 23 % for 6-10 years and 11-20 years respectively. Majority (76.2%) are PHE specialist though 8.2 % are specialist in other subjects. Sixty percent of the schools spend 2 period (11/2 hours) teaching theory, 45 minutes respectively on physical activities and games a week. A minimum of 1-45 minutes respectively on physical activities and games a week. A minimum of 1-9 weeks is spent by 42.6% of the schools on inter-house sports whereas 28% do not practice at all. Significant difference exists in the extent of exposure to the various components of PHE by schools on inter-house sports whereas 28% do not practice at all. Significant difference exists in the extent of exposure to the various components of PHE by school type. Private schools allocate more periods and hours for theory, health issues and games than public schools. Public schools however spend more weeks on inter-house sport while private schools spend more time. It is therfore, recommended that the status of PHE be elevated, all schools should have a comphrensive plan and structure in place to enable them execute a comprehensive physical education programme to all students, while some PHE teachers where they are as many as eight in a school, should be redeployed to schools where their services are needed.